Proteomic selection of immunodiagnostic antigens for Trypanosoma congolense. - Jennifer R Fleming; Lalitha Sastry; Thomas W M Crozier; Grant B Napier; Lauren Sullivan; Michael A J Ferguson (Public Library of Science (PLoS), 2014)
Animal African Trypanosomosis (AAT) presents a severe problem for agricultural development in sub-Saharan Africa. It is caused by several trypanosome species and current means of diagnosis are expensive and impractical for field use. Our aim was to discover antigens for the detection of antibodies to Trypanosoma congolense, one of the main causative agents of AAT. We took a proteomic approach to identify potential immunodiagnostic parasite protein antigens. One hundred and thirteen proteins were identified which were selectively recognized by infected cattle sera. These were assessed for likelihood of recombinant protein expression in E. coli and fifteen were successfully expressed and assessed for their immunodiagnostic potential by ELISA using pooled pre- and post-infection cattle sera. Three proteins, members of the invariant surface glycoprotein (ISG) family, performed favorably and were then assessed using individual cattle sera. One antigen, Tc38630, evaluated blind with 77 randomized cattle sera in an ELISA assay gave sensitivity and specificity performances of 87.2% and 97.4%, respectively. Cattle immunoreactivity to this antigen diminished significantly following drug-cure, a feature helpful for monitoring the efficacy of drug treatment.